2018
DOI: 10.1093/ibd/izy269
|View full text |Cite
|
Sign up to set email alerts
|

Cell Trafficking Interference in Inflammatory Bowel Disease: Therapeutic Interventions Based on Basic Pathogenesis Concepts

Abstract: After 20 years of successful targeting of pro-inflammatory cytokines for the treatment of IBD, an alternative therapeutic strategy has emerged, based on several decades of advances in understanding the pathogenesis of IBD. The targeting of molecules involved in leukocyte traffic has recently become a safe and effective alternative. With 2 currently approved drugs (ie, natalizumab, vedolizumab) and several others in phase 3 trials (eg, etrolizumab, ozanimod, anti-MAdCAM-1), the blockade of trafficking molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 93 publications
(135 reference statements)
0
57
0
Order By: Relevance
“…CCR9 has been investigated as potential drug target to hinder the migration of leukocytes, unfortunately with poor outcome [47]. However, it mainly facilitates the migration to the small intestine and has been hypothesized to play a limited role during inflammation since it might be a predominantly homeostatic molecule [48]. Yet, another study by Trivedi and colleagues has shown that the colonic expression of the CCR9 ligand CCL25 is upregulated in patients with active colitis and also correlates with the endoscopic Mayo score [49].…”
Section: Discussionmentioning
confidence: 99%
“…CCR9 has been investigated as potential drug target to hinder the migration of leukocytes, unfortunately with poor outcome [47]. However, it mainly facilitates the migration to the small intestine and has been hypothesized to play a limited role during inflammation since it might be a predominantly homeostatic molecule [48]. Yet, another study by Trivedi and colleagues has shown that the colonic expression of the CCR9 ligand CCL25 is upregulated in patients with active colitis and also correlates with the endoscopic Mayo score [49].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial dysbiosis and gut barrier alteration allow the interaction of microbes with immune cells leading to dysregulated activation of leukocytes and enhanced synthesis of a plethora of molecules (i.e., cytokines and eicosanoids), resulting in constant leukocyte trafficking and massive accumulation of lymphocytes, neutrophils, and (or) macrophages. [ 2 ] This disturbs the ratio of pro‐/anti‐inflammatory molecules, which generates long‐lasting inflammation and contributes to IBD complications such as ulcer formation, fibrosis, and cancer. [ 3,4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 22–24 ] Targeting the synthesis of soluble mediators by immune cells has emerged as an exciting approach in IBDs therapy. [ 2,4 ] The 5‐LOX/COX‐2 pathway (and its HKE 2 and HKD 2 products) offers a new option to advance in the understanding of the molecular mechanisms underlying the effect of Uro against IBDs. In this study, we have studied whether Uro, including Uro‐A, isourolithin‐A (IsoUro‐A), Uro‐B, and Uro‐C, and their most relevant phase‐II conjugates (glucuronides and sulfates) modulate the formation of 5‐LOX (5‐HETE and LTB 4 ), COX‐2 (PGE 2 ), and 5‐LOX/COX‐2 (HKE 2 and HKD 2 ) products in a human isolated leukocyte model.…”
Section: Introductionmentioning
confidence: 99%
“…Sphingosine 1-phosphate (S1P) is a membrane-derived lysophospholipid signaling molecule involved in regulation of multiple physiologic and pathophysiologic processes, mediated through the 5 isoforms of the G protein-coupled S1P receptor (S1P 1 through S1P 5 ). 4,5 The function of each receptor is highly dependent on the cell type on which it is expressed. S1P 1 , S1P 2 , and S1P 3 are widely expressed throughout the body, whereas S1P 4 and S1P 5 have more limited expression in immune and central nervous system cell subsets.…”
mentioning
confidence: 99%
“…32,33 Newer S1P receptor modulators with selective receptor isoform affinities are currently in development. 5,21,34 Etrasimod is a selective S1P 1 , S1P 4 , and S1P 5 receptor modulator that is being developed for treatment of immunemediated inflammatory disorders. 34,35 After treatment with once-daily etrasimod 2 mg, an approximately 53% decrease from baseline in mean lymphocyte counts was observed in healthy volunteers at day 3, with a continued decline to 69% by day 21 and lymphocyte recovery to within 5% of baseline 7 days after drug discontinuation.…”
mentioning
confidence: 99%